Clinical Practice Guideline: Otitis Media with Effusion Executive Summary (Update). (February 2016) - Rosenfeld, Richard M.; Shin, Jennifer J.; Schwartz, Seth R.; Coggins, Robyn; Gagnon, Lisa; Hackell, Jesse M.; Hoelting, David; Hunter, Lisa L.; Kummer, Ann W.; Payne, Spencer C.; Poe, Dennis S.; Veling, Maria; et al.
The American Academy of Otolaryngology—Head and Neck Surgery Foundation has published a supplement to this issue of Otolaryngology—Head and Neck Surgery featuring the updated "Clinical Practice Guideline: Otitis Media with Effusion." To assist in implementing the guideline recommendations, this article summarizes the rationale, purpose, and key action statements. The 18 recommendations developed emphasize diagnostic accuracy, identification of children who are most susceptible to developmental sequelae from otitis media with effusion, and education of clinicians and patients regarding the favorable natural history of most otitis media with effusion and the lack of efficacy for medical therapy (eg, steroids, antihistamines, decongestants). An updated guideline is needed due to new clinical trials, new systematic reviews, and the lack of consumer participation in the initial guideline development group.